Historiography of the Problem According Forming Interest to Reading in Pupils in the Process of Activity of School Libraries - Lyudmyla Balika (Pedagogical Discourse, 2013)
The article is devoted to the historical analysis of dissertational researches of Ukrainian and foreign scientists on the problem of development pupils’ reading interest in the process of activity of school libraries. Research works where methods of teaching reading (M.Kobahidze) and formation of reader’s interests (S.Pribilykh), levels of successful reading activity (M.Kiseleva), author’s pedagogical system of development reader’s interests (I.Zhukova) are grounded; the author’s concept of attracting pupils to reading (T.Halaktionova), proposes of modification and adaptation the principles of pedagogic of co-creativity according the features of pupils of primary schools (N.Yegorova) are disclosed; a model of the school library requirements for ensuring information needs (O.Matviychuk), the influence of the ideological factor in the activity of Ukrainian libraries in the period 40-s - 80-s years of the XX century (M.Oreshkina), the main criteria that determined the status of lyceum libraries (V.Mozgova) are analyzed.